A hierarchically multifunctional integrated catalyst with intimate and synergistic active sites for one-pot tandem catalysis. Issue 14 (15th June 2021) - Yao, Yao; Huang, Kexin; Liu, Yi; Luo, Tingting; Tian, Ge; Li, Jiaxin; Zhang, Song; Chang, Ganggang; Yang, Xiaoyu
Abstract : As a typical process-intensive strategy, a tandem reaction driven by a multifunctional catalyst is a paragon of the green catalytic process. Abstract : As a typical process-intensive strategy, a tandem reaction driven by a multifunctional catalyst is a paragon of the green catalytic process. Two or more active sites are usually required and their rational spatial distribution is critical for the multi-functional catalyst to act independently or synergistically. Here, we present a simple and stepwise method to construct a trifunctional integrated catalyst simultaneously with spatially intimate acidic (phosphotungstic acid (HPW)), basic (amino) and metal (Pd nanoparticles (NPs)) sites in hierarchically porous UiO-66-NH2 . Through fine controlling the ratio of immobilized HPW and amino groups, we can easily tune its accessible acidic and basic properties, and the anchored HPW molecules can be effectively used to mediate the catalytic performance of Pd NPs and further stabilize the Pd sites. This well-designed integrated catalyst showed excellent catalytic activity and yield (>97%) towards one-pot three-step Deacetalization–Knoevenagel–Hydrogenation (D–K–H) catalysis reactions owing to the synergetic catalysis and the intimate spatial arrangement of the acid, basic and metal sites. More importantly, the trifunctional catalyst could be recycled at least five times without significantly losing its activity due to the strong interaction between the MOF and the guest molecules. This work provides some important insights into the construction of multifunctional integrated catalysts, especially for the application in challenging tandem catalysis.